The Influence of Motivation and Discipline on Employees' Work Productivity at PT Mowilex Indonesia Jakarta Barat - Prabowo, Budhi; Yuliana, Tri; Darmawan, Aulia; Pratama, Guruh Dwi; Wahyudi, Yuli (Universitas Pamulang, 2023)
The purpose of this study was to determine the effect of motivation and discipline on the work productivity of employees at PT Mowilex Indonesia, West Jakarta. The method used is quantitative. The sampling technique used saturated sampling and obtained a sample of 68 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. The results of this study are that motivation has a significant effect on employee work productivity with a determination coefficient value of 48.8% and the hypothesis test is obtained t count > t table or (7.938 > 1.987). Discipline has a significant effect on employee work productivity with a determination coefficient value of 47. 8% and hypothesis testing obtained t count > t table or (7,775 > 1,987). Motivation and discipline simultaneously have a significant effect on employee productivity with the regression equation Y = 8.109 + 0.387X1 + 0.428X2. The coefficient of determination is 64.8% while the remaining 35.2% is influenced by other factors. Hypothesis testing obtained F count > F table or (59,888 > 2,750).